2023
DOI: 10.1177/03000605231187802
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hematological parameters and bronchopulmonary dysplasia in premature infants

Abstract: Objective To evaluate the association between hematological parameters on the first day of life and bronchopulmonary dysplasia (BPD) in preterm infants. Methods This retrospective study involved all premature infants admitted to our neonatal intensive care unit from January 2017 to June 2022. BPD was diagnosed based on hypoxia exposure for ≥28 days. The neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), platelet count (PLT), mean platelet volume (MPV), and platelet mass index (PMI) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Previous research indicated that Many biomarkers, such as CRP, and PCT, could be used in the auxiliary diagnosis of sepsis, but their serum levels may be affected by many other stimulations other than infection. [ 22 24 ] therefore, compared with HDL and LDL, their predictive abilities appeared low. That’s consistent with our research.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicated that Many biomarkers, such as CRP, and PCT, could be used in the auxiliary diagnosis of sepsis, but their serum levels may be affected by many other stimulations other than infection. [ 22 24 ] therefore, compared with HDL and LDL, their predictive abilities appeared low. That’s consistent with our research.…”
Section: Discussionmentioning
confidence: 99%
“…Summarizing the data obtained, it should be noted that the indicators of erythrocytes, hemoglobin, hematocrit and platelets were inversely correlated with the GW of newborns and had statistically signifi cantly lower values compared to control values (p<0. 0001), probably indicating a weak adaptive response to the combined eff ect of intra-and postnatal adverse factors against the background of severe combined somatic dysfunction, and also due to the suppression of hematopoietic activation under the conditions of hypoxia in MFD [25,26]. Levels of leukocytes, especially polymorphonuclear neutrophils (PMN), were statistically signifi cantly higher, which is characteristic of lower GA compared to controls (p<0.0001).…”
Section: Introductionmentioning
confidence: 98%
“…The hematopoietic system plays an important role in providing compensatory and adaptive mechanisms in conditions of premature birth, having certain characteristics in conditions of morphological and functional immaturity of the organism [25,26]. The analysis of the complete blood count (CBC) on the fi rst day of life in premature infants of the observation groups showed that the average values of most indicators diff er between groups of newborns and have a clear correlation with the general condition and GA, respectively.…”
Section: Introductionmentioning
confidence: 99%